1960
DOI: 10.1111/j.1365-2141.1960.tb06252.x
|View full text |Cite
|
Sign up to set email alerts
|

The Quantitative Estiniation of Mechanical Haeniolysis for Clinical Application

Abstract: IN the last century, Meltzer and Welch (1884) had already noticed haeniolysis of erythrocytcs of oxen caused by mechanical trauma. Later, Rous aiid Turner (19 16) investigated erythrocytes of shecp arid dogs and found the resistance to shaking to bc quite unrelated to osmotic rcsistancc. These findtngs, howevcr, drew no further attention until 1944, when Slien, Castle aiid Fleming considered this phcnomcnon of mechanical haemolysis again and described a quantitative method for its mcasuremcnt. They observcd an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

1963
1963
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…We have shown that irrespective of red cell type, an increased exposure to mechanical stress leads to enhanced lysis, as observed previously (63). As expected, normal cell lysis occurred similarly in the presence or absence of oxygen, confirming that AA cells remain unchanged when alterations in oxygen tension take place.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We have shown that irrespective of red cell type, an increased exposure to mechanical stress leads to enhanced lysis, as observed previously (63). As expected, normal cell lysis occurred similarly in the presence or absence of oxygen, confirming that AA cells remain unchanged when alterations in oxygen tension take place.…”
Section: Discussionsupporting
confidence: 89%
“…DC is a numerical representation of red cell deformability, defined by: DC = L/W; where the DC increases as the red cell deformablity increases (61, 62). The flow rates were correlated to the amount of shear stress and plotted with respect to the deformability constant [63]. The data are an average of several trials taken from three different blood samples from three separate donors.…”
Section: Methodsmentioning
confidence: 99%
“…Although the MF test bears the closest physiological resemblance of all currently available in vitro models to red cell fragmentation in vivo [17,19,26], MF has been neglected as a tool for investigating the mechanisms responsible for breakage of normal and G-6-PD deficient erythrocytes. The more popular osmotic fragility test was also employed in our previous studies [8,9] but failed to reveal effects of the model drug metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Since erythrocytes are nearly always under isosmotic conditions in the circulation, osmotic fragility does not seem to represent a good in vitro model for hemolytic phenomena in vivo. MF appears to be a much better in vitro model of the physical stresses to which the erythro cyte is subject in vivo and offers a more relevant index of membrane damage [7,19].…”
Section: Discussionmentioning
confidence: 99%
“…Resistenzprüfungen, a) Mechanische Resistenz nach Schubothe [14]; b) osmotische Resistenz gegen 0,10-0,85 g% Kochsalzlösungen, gemessen 30 min nach Inkubation bei Z im m ertem peratur; c) Spontanhäm olysc im Serum der P roben (Extinktionsm essung bei X -546 nm, D = 10 mm, gegen mitinkubiertes Leerserum).…”
Section: F G Räm Lich Und F K Ir C H H O Ffunclassified